An electronic decision support‐based complex intervention to improve management of cardiovascular risk in primary health care: a cluster randomised trial (INTEGRATE). Issue 9 (26th April 2021) - Webster, Ruth; Usherwood, Tim; Joshi, Rohina; Saini, Bandana; Armour, Carol; Critchley, Sue; Di Tanna, Gian Luca; Galgey, Shane; Hespe, Charlotte M; Jan, Stephen; Karia, Ajay; Kaur, Baldeep; et al.
Abstract: Objectives: To determine whether a multifaceted primary health care intervention better controlled cardiovascular disease (CVD) risk factors in patients with high risk of CVD than usual care. Design, setting: Parallel arm, cluster randomised trial in 71 Australian general practices, 5 December 2016 – 13 September 2019. Participants: General practices that predominantly used an electronic medical record system compatible with the HealthTracker electronic decision support tool, and willing to implement all components of the INTEGRATE intervention. Intervention: Electronic point‐of‐care decision support for general practices; combination cardiovascular medications (polypills); and a pharmacy‐based medication adherence program. Main outcome measures: Proportion of patients with high CVD risk not on an optimal preventive medication regimen at baseline who had achieved both blood pressure and low‐density lipoprotein (LDL) cholesterol goals at study end. Results: After a median 15 months' follow‐up, primary outcome data were available for 4477 of 7165 patients in the primary outcome cohort (62%). The proportion of patients who achieved both treatment targets was similar in the intervention (423 of 2156; 19.6%) and control groups (466 of 2321; 20.1%; relative risk, 1.06; 95% CI, 0.85–1.32). Further, no statistically significant differences were found for a number of secondary outcomes, including risk factor screening, preventive medication prescribing, and risk factor levels. Use of intervention components was low; it was highest for HealthTracker, used at least once for 347 of 3236 undertreated patients with high CVD risk (10.7%). Conclusions: Despite evidence for the efficacy of its individual components, the INTEGRATE intervention was not broadly implemented and did not improve CVD risk management in participating Australian general practices. Trial registration: Australian New Zealand Clinical Trials Registry, ACTRN12616000233426 (prospective).